FAD DIETS AND EATING DISORDERS:THE CONSTRUCTION OF MEANINGS IN THE PURSUIT OF THE "PERFECT BODY" AND "HEALTHY LIFE" - Mariana Fernandes Costa (Universidade do Estado do Rio de Janeiro, 2014)
With the largest recovery of healthy eating and the growing interest of people in relation to diet and body image, we observe the onset of eating disorders, as orthorexia, and the media as a space of disclosure of a perfect body standard andthe magic of fad diets. It is a qualitative research that meetsthe proposed doctoral program with publishable results inbook chapters or journal articles. The articles are linked by a thematic trajectory of constructing of healthy eatingconceptions that permeates the whole of the diets and eating disorders in contemporary society. The methodology followstheoretical and conceptual framework for the analysis of various elements selected from the field during the research,with semiotic analysis techniques, literature review andinterpretative analysis, with analogy between distincts cultural systems. In the first publication, Fad diets: an endless and uninterrupted process ..., were analyzed and discussed fad diets in print magazines and their relationship with theconsumer society. In a second step, it was necessary to understand the charm that fad diets raise in current world. This article, Fad Diets: the sorcerer, magic and its symbolicefficacy corresponds a discussion of the magic fad diets innowadays, drawing an analogy with two texts by Claude Lévi-Strauss. The third article, Orthorexia: the (mis)match betweenhealth and illness, questions the concept of healthy eatingwhich leads to orthorexia. These article presents abiopsychosocial approach through literature review andconceptual reflection of what health is, according to GeorgesCanguilhem, exploring the concepts of medicalization,biopower and biopolitics of Michel Foucault. The fad diets are an alternative, miracle or magic. The fashion and its principles of ephemerality, seduction and differentiation that will drive the opinion, especially the women, to consume the dietevidenced by the media, backed by scientific discourse, part ofan endless and uninterrupted process for search the "perfectbody" and the "healthy living". The elements of fad diets, for the common sense, form a network of enchantment compared to magic rituals described by Lévi-Strauss, as the roles of the sorcerer and bewitched, which are organized around the prosecution to show the effectiveness of a spell in some villages, and the health professionals in these magazines whoare legitimated by knowledge, and the bewitched consumersof magazines who show surprising results that reinforce the idea of healthy eating as something magical, in the currentworld. Subsequently, the orthorexia is the exacerbation of the benefits of a healthy diet. The people assume eating practicesto detox the body from the purity of food, using a rigorousdiscipline and control of daily food, and creating dietarystandards that lead to isolation and illness, the meaning ofhealth as a power for the construction and adaptation of standards for the good living. The spread of the biopower and biopolitics favors the restriction of a scheme of life, based on the control and safety. The individual is responsible for their choices and illness because it could ward off the health riskswith the medicalization, or with a healthy diet to cleanse theevils. DOI: http://dx.doi.org/10.12957/demetra.2014.14069